Acute leukemia / myelodysplastic syndrome as a sequelae of carcinoma breast: A report of five cases from north India - Bhatia Prateek; Das Reena; Ahluwalia Jasmina; Malhotra Pankaj; Varma Neelam; Varma S; Sharma S; Garewal Gurjeewan (Wolters Kluwer Medknow Publications, 2009)
A second malignant neoplasm has been found to be more frequent than might be expected from the general population rates. Therapy-related myelodysplastic syndrome and acute leukemia are dreaded long-term complications of five cases of hematological malignancies following treatment for successful breast cancer therapy (therapeutic drugs or radiotherapy). We encountered carcinoma from north India over a 7-year period from 1999 to 2005. The patients presented 2-5 years after treatment of breast carcinoma. Three patients underwent surgery and received chemoradiotherapy. One patient received chemotherapy after surgery. One patient underwent only surgery and after 3 years presented with acute myeloid leukemia and bone marrow metastasis of carcinoma of the breast. At the time of presentation, all the patients had either bicytopenia or pancytopenia. A close follow-up with complete blood cell counts of the patients who previously had carcinoma of the breast is suggested for early detection of hematological abnormalities. However, the poor prognosis, limited financial resources and poor health insurance coverage results in few patients and their family members opting for treatment.